Overcoming the gap in technology integration in limited conditions in rural classrooms - Pan, Hailin; Lin, Qian; Zhu, Wenfang (The Journal of educational research (Washington, D.C.), 2025)
The objective of the current research is to empirically examine whether the integration of digital technologies into the educational process can indeed be regarded as a means to bridge the existing gap, employing a quasi-experimental design with control, experimental, and comparative groups of elementary school students. The study involved 360 children from second and third grades of both rural and urban schools. The final annual academic grades in four subjects served as the primary indicator for comparing the academic performance of the students. The t-test results demonstrate statistically significant improvements in the experimental (B) and comparative (C) groups across the four investigated subjects, with a p value of .000. Specifically, the experimental group increased average scores by 6.68 in the Chinese language, 5.45 in mathematics, 6.95 in the English language, and 7.41 in the natural sciences. A one-way analysis of variance revealed significant intergroup differences in actual scores post-intervention (p = .000).